Analisis Penerapan Akuntansi Persediaan Berdasarkan PSAK 14 (Studi Kasus PT Garudafood Putra Putri Jaya Tbk) - Ariq Rahman, Muhammad; Ningrum, Nur Indah Kusuma; Lia Uzliawati (Prodi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas PGRI Madiun, 2024)
This study aims to analyze the application of inventory accounting based on PSAK 14 with a case study at PT Garudafood Putra Putri Jaya Tbk. The method used in this research is descriptive qualitative method with case study approach. The results showed that PT Garudafood Putra Putri Jaya Tbk applies the principles of inventory accounting in accordance with the provisions of PSAK 14. The practical implication of this research is the importance of companies to understand and follow applicable accounting standards so that the presentation of financial statements becomes more accurate and transparent